Three essays on finance - Xia, Chongwu (2016)
In essay one, we present a theory of endogenous coalition formation in financial markets, which highlights the information sharing and market competition features of coalitions. Allied members enjoy benefits of information advantage and monopolistic power in trading, but forming coalitions incurs direct costs of setting up coalitions and indirect costs from market liquidity dry-ups. Such a trade-off determines the coalition structure of the economy. As allied members behave more monopolistically, coalitions have negative effects on price informativeness and market liquidity. From the information perspective, financial intermediaries (e.g., asset management companies in the mutual fund industry) can be viewed as coalitions of market players (e.g., fund managers). Our theory provides novel insights about the structure of this industry. In essay two, we examine the influence of covenant violations on violation firms’ alliance activities. We find that firms witness a decline in the number of strategic alliances (especially joint ventures) in the years following debt covenant violations. The causality is established through difference-in-difference regressions and the regression discontinuity design. Our findings support the argument that covenant violation can be detrimental to a firm’s reputation, deterring potential partner firms from forming alliances with violation firms. This study contributes to covenant violation research by highlighting the ramifications of reputation damage triggered by covenant violation on corporate alliance activities. In essay three, we focus on the IPO market, and examine the influence of corporate hedging on firm value. Since corporate hedging reduces information asymmetry of IPO firms, we find that the issuers with corporate hedging have less information to extract from informed investors and are associated with lower price revision and underwriting fee. More importantly, corporate hedging is found to reduce IPO underpricing, which provides evidence that hedging increases firm value particularly during the issuing process. We also provide further evidence that corporate hedging increases firm value through the channel of reducing information asymmetry and value uncertainty, by documenting that hedging reduces the aftermarket idiosyncratic volatility and enhances aftermarket liquidity and long-term performance.